2021
DOI: 10.1155/2021/5547092
|View full text |Cite
|
Sign up to set email alerts
|

Chinaʼs Economic Growth, Energy Efficiency, and Industrial Development: Nonlinear Effects on Carbon Dioxide Emissions

Abstract: This paper analyzes the time-varying impacts of Chinaʼs economic growth, energy efficiency, and industrial development on carbon dioxide (CO2) emissions from 1970 to 2019. First, we examined and found that there are two significant structural changes in the CO2 sequence over the years, and there was a significant nonlinear relationship among the four. The first nonlinear structural model constructed is the TVP regression model. According to the Bayesian model comparison criterion, TVP-SV-VAR was selected as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…(3) Industrial development (lnind) is a key factor affecting carbon emissions [65]. The high energy consumption characteristics of industrial development can have a significant impact on carbon emissions [69]. In addition, Chao et al found that the expansion of tourism would lead to deindustrialization [70].…”
Section: Variables Of the Structural Equation Modelmentioning
confidence: 99%
“…(3) Industrial development (lnind) is a key factor affecting carbon emissions [65]. The high energy consumption characteristics of industrial development can have a significant impact on carbon emissions [69]. In addition, Chao et al found that the expansion of tourism would lead to deindustrialization [70].…”
Section: Variables Of the Structural Equation Modelmentioning
confidence: 99%
“…An analysis of the models used in energy efficiency is provided by Refs. [39,40]. The majority of the studies in terms of regional convergence of energy productivity focus on Chinese provinces.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the both trade openness, industrial development and construction as independent variables in terms of testing the EKC hypothesis, there is no works by using two variables together. However, if those variables considered separately as independent variables, there are some researches (Adedoyin et al, 2022;Ali, et al, 2021;Li and Haneklaus, 2022;Zhou, et al, 2021) in the academic literature. While generating this part, besides examining the most recent work, researches on different economies are considered as well.…”
Section: Literature Reviewmentioning
confidence: 99%